2010
DOI: 10.1002/chem.201001078
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Lewis Acid versus Lewis Base Catalysis in Asymmetric Cyanohydrin Synthesis

Abstract: The asymmetric addition of trimethylsilyl cyanide to aldehydes can be catalysed by Lewis acids and/or Lewis bases, which activate the aldehyde and trimethylsilyl cyanide, respectively. It is not always apparent from the structure of the catalyst whether Lewis acid or Lewis base catalysis predominates. To investigate this in the context of using salen complexes of titanium, vanadium and aluminium as catalysts, a Hammett analysis of asymmetric cyanohydrin synthesis was undertaken. When Lewis acid catalysis is do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 69 publications
3
21
0
Order By: Relevance
“…It is also consistent with the first‐order kinetics observed with respect to catalyst 11 as the catalytic cycle involves bimetallic complex 21 . The greater catalytic activity of complex 11 compared to aluminium complex 9 can be explained by the higher Lewis acidity of 11 25…”
Section: Resultsmentioning
confidence: 99%
“…It is also consistent with the first‐order kinetics observed with respect to catalyst 11 as the catalytic cycle involves bimetallic complex 21 . The greater catalytic activity of complex 11 compared to aluminium complex 9 can be explained by the higher Lewis acidity of 11 25…”
Section: Resultsmentioning
confidence: 99%
“…For asymmetric cyanohydrin synthesis catalysed by 4 , the structure of the anion significantly influences the catalytic activity, though not the enantioselectivity. The best results were obtained by using complexes with a nucleophilic counter-ion that was capable of acting as a Lewis base to activate the trimethylsilyl cyanide 30, 32, 33, 35. Therefore, 4 b – f were screened as catalysts for the synthesis of 6 a under the conditions of Table 1, entry 13.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanistic studies27 showed that the active species in both of these systems was actually the bi-metallic complex 3 and just 0.1 mol % of 3 was able to catalyse the asymmetric addition of trimethylsilyl cyanide to aldehydes in less than one hour at room temperature 28, 29. Based on the mechanistic information obtained with titanium complexes,27, 30 we were able to develop vanadium(V)(salen) complexes 4 as even more enantioselective catalysts for the asymmetric addition of trimethylsilyl cyanide to aldehydes 2935. In view of this precedent, we decided to investigate whether structurally well-defined metal(salen) complexes 3 and 4 might form highly active and enantioselective catalysts for the asymmetric addition of trimethylsilyl cyanide to nitroalkenes and in this paper we report the results of this work.…”
Section: Introductionmentioning
confidence: 99%
“…[26] A synthetic procedure that involves the cyanation of 3,4-dichlorobenzaldehyde might seem less attractive since the acetylated cyanohydrin from 3,4-dichlorobenzaldehyde has previously been prepared in merely 40 % yield and 93 % ee by enzymatic kinetic resolution of the racemic compound, [27] whereas the corresponding trimethylsilyl (TMS) ether was obtained with 78 % ee in connection to mechanistic studies. [28] Our results from an exploration of a route for the synthesis of these b blockers based on acylcyanation of prochiral aldehydes 2 a-c by employing the two-catalyst minor enantiomer recycling procedure are reported here.…”
Section: Introductionmentioning
confidence: 99%